The Effect of Environmental Sustainability Factors, Funding Models, and Risk Management on Social Entrepreneurship Success: A Case Study on CV. Pangalusna Sukabumi - Sunarni Sunarni (Westscience Press, 2023)
This study investigates the complex mechanisms that impact the achievement of social entrepreneurship endeavors, concentrating on the case of CV. Pangalusna Sukabumi. The study investigates the relationships between environmental sustainability factors, funding models, risk management, and social entrepreneurship success via quantitative analysis involving 213 participants. The findings demonstrate statistically significant positive correlations, suggesting that social entrepreneurship endeavors of organizations dedicated to environmental sustainability, employing a variety of funding models, and executing efficient risk management strategies are more likely to be prosperous. This study makes a valuable contribution to the current body of literature by providing empirically validated insights. It also offers practical guidance for policymakers, practitioners, and researchers who are interested in improving the sustainability and effectiveness of social entrepreneurship initiatives.